About the Mechanism of Mammalian Erythrocytes Osmotic Stability - Shpakova, Natalia; Orlova, Natalia (Problems of Cryobiology and Cryomedicine, 2020)
Abstract: The peculiarities of the eﬀect of hypertonic shock and hypotonic stress on erythrocytes of diﬀerent species of mammals (human, bull, horse, rabbit, dog, rat) have been investigated. Based on the results of correlation analysis (using the Spearman’s rank correlation coeﬃcient), the relationship between osmotic sensitivity of mammalian erythrocytes and the well-known structural and functional characteristics of these cells was assessed. The paper presents and analyzes the signiﬁcant relationships. Under hypotonic stress of mammalian erythrocytes, the values of the threshold concentration of NaCl and the one of osmotic fragility were found to correlate with the size of cells (diameter). Under hypertonic shock of mammalian erythrocytes, the values of the threshold concentrations of NaCl and that of hemolysis of cells in a medium containing 4.0 mol/L NaCl correlated with the membrane permeability to water. Mammalian erythrocytes with a high value of the coeﬃcient of diﬀusion water transport due to the protein channels are more resistant to hypertensive shock. Probl Cryobiol Cryomed 2020; 30(4): 331–342